Self-organized growth of germanium nanocolumns. (2nd March 2017) - Mussabek, G K; Yermukhamed, D; Dikhanbayev, K K; Schleusener, A; Mathur, S; Sivakov, V
Abstract: The crystalline germanium nanostructures were obtained on a silicon surface by the chemical vapor deposition technique using a germanium (IV) iso -propoxide ([Ge(O i Pr)4 ]) metalorganic precursor as a germanium source. As was observed, the one-dimensional (1D) germanium nanostructures on the silicon surface form without using a metal catalyst, meaning that the formation of 1D nanostructures is based not on a vapor–liquid–solid (VLS) growth mechanism, but on self-organization processes which take place on the silicon surfaces during the CVD process of germanium iso -propoxide pyrolysis. Our observation suggests that the non-catalytic growth of germanium nanocolumns is strongly dependent on the CVD process temperature. The germanium phase composition and morphology have been investigated by x-ray diffraction (XRD) and x-ray photoelectron spectroscopy (XPS), and high resolution scanning electron microscopy (HRSEM), respectively. Our results provide a new way to grow 1D germanium nanostructures without contamination by a catalyst, which the vapor–liquid–solid growth mechanism is known to cause, allowing for the application of such materials in micro- and optoelectronics.